If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 + -4x = 5x + 10 Reorder the terms: -35 + -4x = 10 + 5x Solving -35 + -4x = 10 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -35 + -4x + -5x = 10 + 5x + -5x Combine like terms: -4x + -5x = -9x -35 + -9x = 10 + 5x + -5x Combine like terms: 5x + -5x = 0 -35 + -9x = 10 + 0 -35 + -9x = 10 Add '35' to each side of the equation. -35 + 35 + -9x = 10 + 35 Combine like terms: -35 + 35 = 0 0 + -9x = 10 + 35 -9x = 10 + 35 Combine like terms: 10 + 35 = 45 -9x = 45 Divide each side by '-9'. x = -5 Simplifying x = -5
| -7z+6=56-2z | | (x-6)/2=75 | | -4+11n=40 | | 4x+62=7x-24 | | 18-(-4y)=8 | | 12a-16=8a+4 | | 5k-1=24 | | y+7(-2)=11 | | B=nx+x | | 5x+17=2x+5 | | 8.00(4.00+x)=3 | | y+7(0)=11 | | 14x^4y^7/6x^5y^4 | | 3x+12=24-2x | | 5=-3+m/8 | | 2b+6=10 | | y+7(4)=11 | | 4x+-5=2(2x+1) | | 8x+10x=44 | | 4(b-1)+2(3+b)=9 | | 0=8y-56 | | 5x+51=x+19 | | 5+9z=10+9z | | x+100+45=180 | | 144t^2+1/t^2+24 | | 2x-(56)=5 | | 144t^2+1/t^2 | | -12x-3=27-9x | | (12-15n)/(5n^2+6n-8) | | k/3=-17 | | c-68=-121 | | ((x+7)/(x+3))=((x-2)/(x+1))+1 |